Analisis Dampak Sosial dan Lingkungan Pabrik Pati Singkong terhadap Desa Derongisor: Potensi Ekonomi atau Tantangan Pengelolaan - Novi Aryanti; Novia Eliza; Akbar Fauzi Ismail; Aisar Imro’ah Tabah Nisfi R; Andriana Noerwahid Hakim; Arti Lidiawati; Muhammad Ihza Maula; Reska Okta Nur Saputra; Wijayanto Wijayanto (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Derongisor Village in Mojotengah District, Wonosobo Regency, has significant economic potential through the development of a cassava starch processing plant. This industry contributes significantly to increasing community income and creating new jobs. However, the factory's operations also have negative impacts in the form of environmental pollution from solid and liquid waste that disrupts water and air quality around the village. This study uses an Asset-Based Community Development (ABCD) approach to empower the community to manage their economic potential while addressing industrial waste issues sustainably. The study results show that with increased capacity and synergy between the community, the environmental agency, the village government, and academics, waste management can be improved, thus minimizing pollution without sacrificing village economic development. This local asset-based empowerment model effectively creates a balance between economic growth and environmental preservation in Derongisor Village. This study is expected to serve as a strategic reference in the development of a sustainable agricultural processing industry in similar areas.